Analisis Indek Kepuasan Masyarakat Terhadap Pelayanan Publik Pada Dinas Penanaman Modal Dan Pelayanan Terpadu Satu Pintu Kabupaten Bengkulu Selatan - Peringki, Peringki; Soleh , Ahmad; Fitriano , Yun (Sekolah Tinggi Ilmu Ekonomi Bentara Persada, 2024)
Basically, the Indonesia government system places service as the basis for improving bureaucratic relations between the state and society, which is planced in the service government system as a from of achieving common goals which of course need special attention in order to achieving the nation’s ideal. The purpose of this research is to determine the analysis of the public satisfaction index analysis of public service at the south Bengkulu regency investment and one-stop integrated services The type of research in this research is descriptive. The analytical method in this research uses the measurement of the value of the Community Satisfaction Index / IKM based on the Regulation of the Minister for Empowerment of State Apparatus and Bureaucratic Reform of the Republic of Indonesia Number 14 of 2017 concerning Regulation of the Minister for Empowerment of State Apparatus and Bureaucratic Reform concerning Guidelines for Preparing Community Satisfaction Surveys for Public Service Providing Units From this research, the 9 elements of service in the South Bengkulu Regency One Stop Investment and Services Service (DPMPTSP) include systems, mechanisms and procedures as well as handling, complaints, facilities and input which are stated to be very good with a conversion index quality value of 88.25 and 85.25 .